Pengendalian Biaya dalam Hubungannya dengan Akuntansi Pertanggungjawaban (Studi Kasus pada Hotel Indra Puri di Bandar Lampung) - Rosmiaty Tarmizi; Margaretha Selvyana; Agus Purnomo (Universitas Bandar Lampung (UBL), 2010)
The purpose of this paper is to investigate the implementation of cost control in conjunction with the hotel operational responsibility accounting in each department, are also able to compare the practices of companies that implemented the existing theories in hotel operating cost control in relation to responsibility accounting. The usefulness of this study is to contribute ideas and materials comparisons on cost controlin conjunction with the accounting responsibility on Hotel Indra Puri. Hotel Indra Puri equip themselves with the organizational structure in the form of line and staff. Structure owned quite clear with the separation of functions and the division of authority and responsibility firmly. But in reporting costs, separation costs into controllable costs and uncontrollable costs have not been done properly. Existing cost reporting system can not be used directly to assess the performance and efficiency of thework of each department head by management. Management through its Chief Accountant must process the data in order to direct